2014
DOI: 10.1016/j.parkreldis.2014.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Does a specialist unit improve outcomes for hospitalized patients with Parkinson's disease?

Abstract: ObjectiveSuboptimal management of Parkinson's disease (PD) medication in hospital may lead to avoidable complications. We introduced an in-patient PD unit for those admitted urgently with general medical problems. We explored the effect of the unit on medication management, length of stay and patient experience.MethodsWe conducted a single-center prospective feasibility study. The unit's core features were defined following consultation with patients and professionals: specially trained staff, ready availabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…A recent pilot study prospectively explored the effect of utilizing a specialized Parkinson’s disease care unit (SPDU). This study revealed that fewer medications were omitted, more medications were administered on time, and that patients had a shorter length of stay and a better overall experience [ 26 ]. The authors suggested the need for a larger randomized controlled study to confirm these findings, though admittedly this model would not likely be feasible on a larger scale.…”
Section: Discussionmentioning
confidence: 99%
“…A recent pilot study prospectively explored the effect of utilizing a specialized Parkinson’s disease care unit (SPDU). This study revealed that fewer medications were omitted, more medications were administered on time, and that patients had a shorter length of stay and a better overall experience [ 26 ]. The authors suggested the need for a larger randomized controlled study to confirm these findings, though admittedly this model would not likely be feasible on a larger scale.…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease is a slowly progressive degenerative neurotic disease that develops when brain cells that are responsible for the production of dopamine die (Skelly et al, ). This disease is one of the most important chronic diseases in elderly people.…”
Section: Methodsmentioning
confidence: 99%
“…21 In PD and other movement disorders, there is a tradition of combining measures from different scales in a "unified" format (eg, Unified Parkinson's Disease Rating Scale, Unified Dyskinesia Rating Scale). 44,45 An effort to reconfigure and combine all measures into a unified PD treatment adherence scale is feasible, as the clinimetric and statistic expertise is available in the PD scientific community, 9,46 and many existing measures could be used to create this unified approach. The resultant measurement tool would need to accommodate the perspectives from all stakeholders, including patients, caregivers, health providers, and other potential informants.…”
Section: Discussionmentioning
confidence: 99%